THE EDUCATION OF CHILDREN IN THE COURSE MULTIPLE INTELLIGENCES: A RESEARCH PROPOSAL FOR THE CONSTRUCTION OF KNOWLEDGE ENVIRONMENTS CHAMBERS (Fiep Bulletin - online, 2011)
The Municipal School of Alana de Souza Barboza, implemented a new work proposal through Multiple Intelligences, which takes place through a classroom for a daily carvery. So much for the proposal and educational projects aimed at development environments in the rooms, always indicating the ecological approach in the Amazon is home to this project. The appreciation of the Amazonian culture is also carried out educational projects through the issue are the legends of the Amazon folklore, legends identify these room environments, causing the children to identify with the culture because it is the driving force all knowledge and more children in school way of identifying his legend as part of the rotation.
Keywords: Rooms environments; Multiple Intelligences; Caster; legends; Amazonas